2007
DOI: 10.1104/pp.107.113480
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Conversion of Phytate to Inorganic Phosphorus in Soybean Seeds Expressing a Bacterial Phytase

Abstract: Phytic acid (PA) contains the major portion of the phosphorus in the soybean (Glycine max) seed and chelates divalent cations. During germination, both minerals and phosphate are released upon phytase-catalyzed degradation of PA. We generated a soybean line (CAPPA) in which an Escherichia coli periplasmic phytase, the product of the appA gene, was expressed in the cytoplasm of developing cotyledons. CAPPA exhibited high levels of phytase expression, $90% reduction in seed PA, and concomitant increases in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 43 publications
4
67
1
Order By: Relevance
“…Ali et al (2013) also developed low-phytate rice with no apparent developmental defects by seed-specific silencing of IPK1. However, defects in seed weight, germination frequency, and seedling emergence were observed in several other trials, reflecting a role for InsP 6 in seed development (Bilyeu et al, 2008;Kuwano et al, 2009;Li et al, 2014). In this study, we have shown that expression of InsP 6 -sensitive Gle1 variants enhanced plant growth, seed yield, and seed performance of the phytate-deficient ipk1 mutant, suggesting a novel strategy for improving lpa plants.…”
Section: Discussionmentioning
confidence: 76%
“…Ali et al (2013) also developed low-phytate rice with no apparent developmental defects by seed-specific silencing of IPK1. However, defects in seed weight, germination frequency, and seedling emergence were observed in several other trials, reflecting a role for InsP 6 in seed development (Bilyeu et al, 2008;Kuwano et al, 2009;Li et al, 2014). In this study, we have shown that expression of InsP 6 -sensitive Gle1 variants enhanced plant growth, seed yield, and seed performance of the phytate-deficient ipk1 mutant, suggesting a novel strategy for improving lpa plants.…”
Section: Discussionmentioning
confidence: 76%
“…Denbow et al (1998) have observed an improved bioavailability of phytate-P from soybeans transformed with a fungal phytase gene to broilers. Bilyeu et al (2008) have reported that the cytoplasmic expression of an active appA phytase enzyme in developing soybean seeds resulted in the conversion of nearly all seed phytic acid to inorganic P and produced abundant active enzyme in mature seeds capable of releasing significant amounts of phytate-P from soybean meal.…”
Section: Synergism Of Soybean and Phytase In Nutritionmentioning
confidence: 99%
“…This does not only result in non-optimal levels of phosphorus and minerals, but also contributes to wastewater pollution. As supplementation is costly and seems to contribute to the pollution problem, one might prefer to make use of a soybean strain expressing a bacterial phytase, resulting in the production of utilizable inorganic phosphorus (Bilyeu et al, 2008). Soybeans are also a known source of vitamin E and folate.…”
Section: Nutritional Fortification Strategiesmentioning
confidence: 99%